Interfacility transfers for US ischemic stroke and TIA, 2006–2014. (1st May 2018) - George, Benjamin P.; Doyle, Sara J.; Albert, George P.; Busza, Ania; Holloway, Robert G.; Sheth, Kevin N.; Kelly, Adam G.
Abstract : Objective: To investigate changes in emergency department (ED) transfers for ischemic stroke (IS) and TIA. Methods: We performed a retrospective observational study using the US Nationwide Emergency Department Sample to identify changes in interfacility ED transfers for IS and TIA from the perspective of the transferring ED (2006–2014). We calculated nationwide transfer rates and individual ED transfer rates for IS/TIA by diagnosis and hospital characteristics. Hospital-level fractional logistic regression examined changes in transfer rates over time. Results: The population-estimated number of transfers for IS/TIA increased from 22, 576 patient visits in 2006 to 54, 485 patient visits in 2014 ( p trend < 0.001). The rate of IS/TIA transfer increased from 3.4 (95% confidence interval [CI] 3.0–3.8) in 2006 to 7.6 (95% CI 7.2–7.9) in 2014 per 100 ED visits. Among individual EDs, mean transfer rates for IS/TIA increased from 8.2 per 100 ED visits (median 2.0, interquartile range [IQR] 0–10.2) to 19.4 per 100 ED visits (median 8.1, IQR 1.1–33.3) (2006–2014) ( p trend < 0.001). Transfers were more common among IS. Transfer rates were greatest among rural (adjusted odds ratio [AOR] 3.05, 95% CI 2.56–3.64) vs urban/teaching and low-volume EDs (AOR 7.49, 95% CI 6.58–8.53, 1st vs 4th quartile). The adjusted odds of transfer for IS/TIA increased threefold (2006–2014). Conclusions: Interfacility ED transfers for IS/TIA more than doubled from 2006 to 2014. Further work should determine the necessity of IS/TIA transfers and seek to optimize the US stroke care system.